2017
DOI: 10.3390/ijms18091857
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 Sulfotyrosine Enhances CCL21 Binding

Abstract: Chemokines are secreted proteins that direct the migration of immune cells and are involved in numerous disease states. For example, CCL21 (CC chemokine ligand 21) and CCL19 (CC chemokine ligand 19) recruit antigen-presenting dendritic cells and naïve T-cells to the lymph nodes and are thought to play a role in lymph node metastasis of CCR7 (CC chemokine receptor 7)-expressing cancer cells. For many chemokine receptors, N-terminal posttranslational modifications, particularly the sulfation of tyrosine residues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…It was also reported that de-glycosylation with enzymes produced by DCs changed the folding of CCR7 protein to increase the activity of this receptor (9). Conversely, the induction of sulfation in tyrosine residue of the CCR7 protein N-terminus can increase the affinity between CCR7 and its ligands (72).…”
Section: Epigenetic and Post-translational Modification (Ptm) Of Ccr7mentioning
confidence: 99%
“…It was also reported that de-glycosylation with enzymes produced by DCs changed the folding of CCR7 protein to increase the activity of this receptor (9). Conversely, the induction of sulfation in tyrosine residue of the CCR7 protein N-terminus can increase the affinity between CCR7 and its ligands (72).…”
Section: Epigenetic and Post-translational Modification (Ptm) Of Ccr7mentioning
confidence: 99%
“…The binding influences intra-cellular signaling pathways including Janus kinase (JNK), mitogen activated protein kinase (MAPK), extracellular signal-regulated kinase (ERK), and protein kinase B (AKT). It plays an important role, in addition to chemotaxis, in cell survival, cellular proliferation, and metastatic spread of cancer cells that express CXCL12, leading to the formation of secondary colonies [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], and a particular role in HIV infection has also been discovered. Cancer cell metastasis contributes to most of the mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ubiquitylation of CCR7 has been found to control receptor trafficking and hence cell migration . Tyrosine sulfation in the N‐terminus of CCR7 was recently identified to significantly enhance CCL21 binding . In addition, polysialylation of CCR7 was found to be essential for CCL21 recognition and hence dendritic cell homing to lymph nodes .…”
Section: Introductionmentioning
confidence: 99%
“…12 Tyrosine sulfation in the N-terminus of CCR7 was recently identified to significantly enhance CCL21 binding. 13 In addition, polysialylation of CCR7 was found to be essential for CCL21 recognition and hence dendritic cell homing to lymph nodes. 14 Moreover, we identified that distinct glycosylation patterns on CCR7's N-terminus and third extracellular loop shape receptor signaling and endocytosis to control leukocyte migration by CCL19 and CCL21.…”
mentioning
confidence: 99%